Encyclopedia of meat sciences (Elsevier/Academic Press, 2014)
This encyclopedia covers the core theories, methods, and techniques employed by meat scientists and their related applications currently used in research and industry.
Keywords: Meat industry and trade.; Meat.; elektronické knihy; electronic books